Exploring young women's reasons for adopting intrauterine or oral emergency contraception in the United States: a qualitative study - Shelly Kaller; Aisha Mays; Lori Freedman; Cynthia C. Harper; M. Antonia Biggs (BMC, 2020)
Abstract Background The recent focus on increasing access to long-acting reversible contraceptive methods has often overlooked the diverse reasons why women may choose less effective methods even when significant access barriers have been removed. While the copper intrauterine device (IUD) is considered an acceptable alternative to emergency contraception pills (ECPs), it is unclear to what extent low rates of provision and use are due to patient preferences versus structural access barriers. This study explores factors that influence patients' choice between ECPs and the copper IUD as EC, including prior experiences with contraception and attitudes toward EC methods, in settings where both options are available at no cost. Methods We telephone-interviewed 17 patients seeking EC from three San Francisco Bay Area youth-serving clinics that offered the IUD as EC and ECPs as standard practice, regarding their experiences choosing an EC method. We thematically coded all interview transcripts, then summarized the themes related to reasons for choosing ECPs or the IUD as EC. Results Ten participants left their EC visit with ECPs and seven with the IUD as EC option. Women chose ECPs because they were familiar and easily accessible. Reasons for not adopting the copper IUD included having had prior negative experiences with the IUD, concerns about its side effects and the placement procedure, and lack of awareness about the copper IUD. Women who chose the IUD as EC did so primarily because of its long-term efficacy, invisibility, lack of hormones, longer window of post-coital utility, and a desire to not rely on ECPs. Women who chose the IUD as EC had not had prior negative experiences with the IUD, had already been interested in the IUD, and were ready and able to have it placed that day. Conclusions This study highlights that women have varied and well-considered reasons for choosing each EC method. Both ECPs and the copper IUD are important and acceptable EC options, each with their own features offering benefits to patients. Efforts to destigmatize repeated use of ECPs and validate women's choice of either EC method are needed to support women in their EC method decision-making.